PERTANGGUNGJAWABAN PIDANA NAKHODA KAPAL DALAM KECELAKAAN KAPAL MENURUT UNDANG-UNDANG NOMOR 17 TAHUN 2008 TENTANG PELAYARAN - UTAMI, SUTRI; Erdianto, Erdianto; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Marine transportation in the islands countries should be most requested, because there are islands only be connected through maritime transport, but in Indonesia sea tarnsportasi not managed optimally. Various provisions of the International has been ratified even national provisions also complete, but the implementation of these provisions is still limited to business interests and ignoring the security and safety aspects of shipping. In any event the causes of accidents always publicized accident was human error in this case the vessel skipper, but the general human error is always preceded by human error before shipping. In the numerous event of accident during the cruise ships often announced that the number of passengers is not in accordance with manisfest or even a boat called over-load.The writing of this thesis is entitled "Criminal Liability of Ship Skippers Against Ship Accidents According to Law No.17 of 2008 Concerning Shipping", with the problem of (1) What are the forms of ship accidents, and (2) What is the responsibility of the skipper for ship accidents according to the Law Law No. 17 of 2008 concerning Shipping.This writing uses a normative approach that is descriptive in nature, because this study is a scientific study, and this study uses the statutory approach and case approach, the type of material used is primary legal material, and secondary material.Based on the research results obtained that the forms of ship accidents are: sinking ship, burning ship, collision ship, and aground. And the responsibility of the master of ship accidents is that the skipper takes full responsibility for human / passenger safety, cargo, security and order of the ship. From this writing it is suggested: The master of the ship must be more careful in carrying out his duties on the ship, and must have the competence of a seaman's diploma in accordance with statutory regulations.Keywords : Skipper-ship accident-responsible.